On the farm A Touch & feel story - Dainty, Alice; Gey, Eva Maria; Mowat, Claire (New York igloo books amazing, 2023)
Clara the cow is looking for her friends on the farm. Can you help her find them? with different textures and surprises on every pages, little ones will love exploring this sensory story
English stories
Keywords: English stories